2015
DOI: 10.5603/ep.a2016.0034
|View full text |Cite
|
Sign up to set email alerts
|

Cushing`s disease: Fibrinogen and D-dimer levels fail to normalize despite early postoperative remission — a prospective, controlled study

Abstract: Introduction: Effective transsphenoidal surgery (TSS) for Cushing`s disease (CD) normalizes cortisol levels and reduces complications of hypercortisolism. However, there is evidence of increased cardiovascular morbidity even after successful surgery. Objective. A prospective, controlled study on the dynamics of fibrinogen and D-dimer levels with a six-month follow-up after an effective TSS for CD. Material and methods: Forty patients with CD and forty healthy age-and sex-matched subjects were included. We asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
(52 reference statements)
1
11
0
Order By: Relevance
“…The Cushing's disease was confirmed based on a serum cortisol and UFC suppression greater than 50% on high dose dexamethasone suppression test (HDDST; 2 mg q.i.d. for 48 h) and a positive result of stimulation test (increase in plasma cortisol level >20% above basal and serum ACTH level >50% above basal) with intravenous CRH injection (100 μg) and positive MR imaging for pituitary tumor as previously described in the literature (20,21). In cases of negative or equivocal MRI results (intrasellar lesion ≤6 mm), bilateral inferior petrosal sinus sampling (BIPSS) was performed as a routine investigation tool.…”
Section: Patients' Populationmentioning
confidence: 99%
“…The Cushing's disease was confirmed based on a serum cortisol and UFC suppression greater than 50% on high dose dexamethasone suppression test (HDDST; 2 mg q.i.d. for 48 h) and a positive result of stimulation test (increase in plasma cortisol level >20% above basal and serum ACTH level >50% above basal) with intravenous CRH injection (100 μg) and positive MR imaging for pituitary tumor as previously described in the literature (20,21). In cases of negative or equivocal MRI results (intrasellar lesion ≤6 mm), bilateral inferior petrosal sinus sampling (BIPSS) was performed as a routine investigation tool.…”
Section: Patients' Populationmentioning
confidence: 99%
“…Cortisol excess is a potentially life-threatening condition leading to significant mortality, morbidity, and decreased quality of life. Patients with CD commonly develop metabolic complications such as dyslipidaemia, insulin resistance, prediabetes, and diabetes, along with hypertension and hypercoagulability, which overall result in increased mortality from cardiovascular disease compared to the general population [3][4][5][6]. Fur-…”
Section: Introductionmentioning
confidence: 99%
“…Witek et al 20 showed that 6 months after successful transsphenoidal management of CD, the levels of both fibrinogen and D-dimer remained elevated despite normalization of cortisol levels. However, in another study comparing preoperative and postoperative coagulative parameters in patients with CS, Manetti et al 18 found that after successful surgical treatment, the levels of vWF, thrombin-antithrombin complex, ATIII, PAI-1, α(2) and antiplasmin as well as aPTT normalized at 12 months after surgery.…”
Section: Discussionmentioning
confidence: 99%